Penegakan Hukum Tindak Pidana Pertambangan Emas dan Tembaga Tanpa Izin di Wilayah PT Freeport Indonesia - Desthiny Elsina Angelita Wayoi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This thesis is the result of a study that describes gold mining as a natural resource controlled by the State used for the welfare of the people as a whole. In reality, Illegal Gold Mining (PETI) in Mimika Regency, Central Papua Province is increasingly occurring. The activities of miners who do not have permits have become their main/permanent job. By looking at this problem, the perpetrators of illegal gold mining have clearly violated the legal regulations on mineral and coal mining. However, in reality, what is happening in Mimika Regency is that there are still many gold mining perpetrators who do not have permits. The research method used is a qualitative method with data collection techniques through literature studies and field studies including observation and interviews. The final results are determined using the Miles and Huberman model data analysis technique. The results of this study are How is the current law enforcement and why law enforcement against illegal gold mining (PETI) in Mimika Regency is not optimal, how is the ideal law enforcement in the future?